APOE genotype and early β-amyloid accumulation in older adults without dementia. (5th September 2017) - Lim, Yen Ying; Mormino, Elizabeth C.
Abstract : Objective: To clarify associations between APOE ε4 allele and age on longitudinal rates of β-amyloid (Aβ) accumulation within Aβ+ and Aβ− older individuals without dementia. Methods: We analyzed 595 older adults without dementia classified cross-sectionally as Aβ− (n = 325) and Aβ+ (n = 270) using longitudinal florbetapir PET. The influence of age and APOE genotype on longitudinal accumulation of Aβ was examined with linear mixed models. Results: APOE ε4 and older age were associated with higher risk of being classified as Aβ+ at baseline. The annual rate of Aβ accumulation was significantly greater than zero for Aβ− ε3 (0.0021 ± 0.0007 standardized uptake value ratio [SUVR] units) and Aβ− ε4 (0.0044 ± 0.0010 SUVR units), as well as Aβ+ ε3 (0.0141 ± 0.0019 SUVR units) and Aβ+ ε4 (0.0126 ± 0.0018 SUVR units). Aβ accumulation was significantly faster in Aβ− ε4 compared to Aβ− ε3 and Aβ− ε2. Rates of Aβ accumulation did not differ significantly between Aβ+ APOE groups. Older age was associated with higher rates of Aβ accumulation in the Aβ− group. Conclusions: APOE ε4 carriage and older age were predictors of longitudinal Aβ accumulation within the Aβ− group but not the Aβ+ group. APOE ε2 carriage was protective against longitudinal Aβ accumulation within the Aβ− group. APOE genotype in conjunction with chronologic age may aid in participant selection for primary prevention trials aimed at halting Aβ accumulation before abnormal levels are reached.